Association of OXTR, AVPR1a, LNPEP, and CD38 Genes’ Expression with the Clinical Presentation of Autism Spectrum Disorder - Krzysztof Maria Wilczyński; Aleksandra Auguściak-Duma; Aleksandra Stasik; Lena Cichoń; Alicja Kawalec; Małgorzata Janas-Kozik (Current Issues in Molecular Biology, 2023)
Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder that affects social interactions, communication, and behavior. Although the predominant genetic predisposition to ASD seems beyond doubt, its exact nature remains unclear. In the context of social cognition disorders and the basis of ASD, the oxytocinergic and vasopresynergic systems arouse great interest among researchers. The aim of the present study was to analyze gene expression levels for oxytocin and vasopressin receptors, as well as CD38 protein and oxytocinase, in the context of the clinical picture of autism spectrum disorders. The study included 90 people, of whom 63 were diagnosed with ASD based on anamnesis, mental status testing, and the ADOS-2 protocol. The results obtained in the presented study indicate that the balance between the levels of expression of the CD38 gene and the oxytocinase gene plays a key role in the risk and clinical presentation of ASD. In a hypothetical scenario, an imbalance in the expression of CD38 and LNPEP could potentially lead to alterations in the concentrations of oxytocin and vasopressin. At the same time, the most frequently studied genes—AVPR1a and OXTR—seem to be at best of marginal importance for the risk of ASD.